Aqueous electrolyte battery and patch

By employing a porous resin membrane with tailored properties as a separator in aqueous electrolyte batteries, the challenges of load characteristics and reliability are addressed, resulting in improved performance under high current discharge conditions.

JP2025061390AActive Publication Date: 2025-04-10MAXELL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2025006092
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-04-18
Filing Date
2025-01-16
Publication Date
2025-04-10
Estimated Expiration
2040-04-20

AI Technical Summary

Technical Problem

Existing aqueous electrolyte batteries face challenges in achieving excellent load characteristics and reliability, particularly when high current discharge is required, and they are prone to small short circuits due to limitations in separator materials.

Method used

The use of a porous resin membrane with specific thickness, air permeability, and water contact angle as a separator in the aqueous electrolyte battery, which enhances ion permeability and suppresses small short circuits, thereby improving load characteristics and reliability.

Benefits of technology

The proposed solution enables the aqueous electrolyte battery to achieve both excellent load characteristics and high reliability, supporting high current discharge while minimizing the risk of small short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061390000001_ABST
    Figure 2025061390000001_ABST
Patent Text Reader

Abstract

To provide an aqueous electrolyte battery which is excellent in load characteristics and reliability, and a patch including the battery.SOLUTION: There is provided an aqueous electrolyte battery in which a positive electrode, a negative electrode containing a metal material, a separator and an aqueous electrolyte are stored in an exterior body. The separator is a porous film which is made of a resin, and has thickness of 5 μm or more and 100 μm or less, air permeability of 10 sec / 100 mL or more and 3,000 sec / 100 mL or less, and a contact angle of water of 90° or less, and the negative electrode has an electrolyte zinc foil. The patch can be worn on a body, and includes the aqueous electrolyte battery as a power source.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous electrolyte battery having excellent load characteristics and reliability, and a patch including said battery. [Background technology]

[0002] Batteries that use an aqueous electrolyte, such as air batteries and alkaline batteries, are generally either button-shaped with a metal can as an exterior body or cylindrical with a cylindrical exterior can.

[0003] On the other hand, a sheet-type battery using an exterior body made of a resin film has also been produced as a battery having the above-mentioned negative electrode (Patent Document 1, etc.).

[0004] Taking advantage of the shape and other features of such batteries, they are being considered for use as power sources for various body sensors, such as temperature patches. In order to better meet such needs, Patent Document 1 uses an electrolyte with a low pH so that the impact on the environment can be reduced as much as possible when users discard the replaced batteries.

[0005] Incidentally, the use of an electrolyte solution with a low pH as described above tends to reduce the discharge capacity of the battery, but the battery described in Patent Document 1 avoids this problem by using a separator made of a semipermeable membrane such as a resin microporous membrane or nonwoven fabric, or a cellophane film, and whose air permeability is limited to a specific value or higher. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2018 / 056307 Summary of the Invention [Problem to be solved by the invention]

[0007] Incidentally, in recent years, applications of batteries having an aqueous electrolyte solution that require discharge at a relatively large current value have been considered. Accordingly, there are cases in which improvement in load characteristics is required. However, the technology described in Patent Document 1 still has room for improvement in this regard.

[0008] On the other hand, it is possible to improve the load characteristics of a battery by using a membrane with very low air permeability and excellent ion permeability, such as a resin nonwoven fabric, as a separator. However, batteries having such separators are prone to micro-short circuits, which reduces their reliability.

[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an aqueous electrolyte battery having excellent load characteristics and reliability, and a patch including the battery. [Means for solving the problem]

[0010] The aqueous electrolyte battery of the present invention comprises a positive electrode, a negative electrode containing a metal material, a separator, and an aqueous electrolyte housed within an exterior body, the separator being a porous film having a thickness of 5 μm to 100 μm, an air permeability of 10 sec / 100 mL to 3000 sec / 100 mL, and a contact angle with water of 90° or less, and the negative electrode having electrolytic zinc foil.

[0011] The patch of the present invention is characterized in that it can be attached to the body and includes the aqueous electrolyte battery of the present invention as a power source. Effect of the Invention

[0012] According to the present invention, it is possible to provide an aqueous electrolyte battery having excellent load characteristics and reliability, and a patch including the battery. [Brief description of the drawings]

[0013] [Figure 1] 1 is a plan view showing a schematic diagram of an example of an aqueous electrolyte battery of the present invention. [Diagram 2] 2 is a cross-sectional view taken along line II in FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The separator of the aqueous electrolyte battery of the present invention is made of a resin and is composed of a porous film having a thickness of 5 μm or more and 100 μm or less, an air permeability of 10 sec / 100 mL or more and 3000 sec / 100 mL or less, and a contact angle with water of 90° or less.

[0015] As described above, when a semipermeable membrane such as a cellophane film is used, it is possible to prevent a decrease in the discharge capacity of the battery, even when an electrolyte solution with a pH of 3 or more and less than 12 is used. On the other hand, although the semipermeable membrane has ion permeability, it is a substantially non-porous membrane with very high air permeability, so that the amount of ions that are responsible for the battery reaction that permeate is limited, and the load characteristics (discharge characteristics under heavy load) of the battery are likely to deteriorate.

[0016] On the other hand, nonwoven fabrics made of resins such as polyolefins have an air permeability of less than 5 sec / 100 mL and very high ion permeability, and although batteries using these as separators can suppress the deterioration of load characteristics, they are prone to micro-short circuits and have poor reliability and storage properties. This is thought to be because separators made of nonwoven fabrics usually have large pores (voids), and the protrusions on the surface of the positive or negative electrode pass through these pores and come into contact with the counter electrode.

[0017] Furthermore, when a microporous membrane made of a resin such as polyolefin, which is commonly used in non-aqueous secondary batteries, is used as a separator, the occurrence of the above-mentioned micro-short circuit can be suppressed better than when a nonwoven fabric is used as a separator, but the load characteristics of the battery are likely to deteriorate as in the case of using a semipermeable membrane as a separator. According to the studies of the present inventors, it was found that the load characteristics are deteriorated because the microporous membrane made of the resin is difficult to wet with an aqueous electrolyte and has poor ion permeability.

[0018] Therefore, in the present invention, a resin porous membrane having a specific thickness, specific air permeability, and a contact angle with water of 90° or less is used as a separator. The porous membrane has a high affinity with "water," which is a solvent constituting an aqueous electrolyte, and has good permeability, so that the amount of ion permeation in the separator is large. Therefore, by using this as a separator, it is possible to obtain a large capacity even when the battery is discharged under a heavy load.

[0019] In addition, since the porous membrane has a high air permeability and a certain degree of limited breathability, and also has a certain degree of thickness, the occurrence of the micro-short circuit can be suppressed in a battery using this as a separator.

[0020] Due to the above-mentioned effects, the aqueous electrolyte battery of the present invention is capable of achieving both excellent load characteristics and maintaining high reliability.

[0021] The porous membrane used as a separator of an aqueous electrolyte battery has a contact angle with water of 90° or less, preferably 70° or less, and particularly preferably 60° or less. If the contact angle with water satisfies such a value and the air permeability is within the range described below, the porous membrane can be used as a separator to improve the load characteristics of the battery because it has high affinity with the aqueous electrolyte and good ion permeability. The lower limit of the contact angle with water of the porous membrane used as a separator is not particularly limited, but is usually 10° or more. In order to expand the types of resins that can be used and the conditions of the hydrophilization treatment to make it easier to manufacture, it is preferably 20° or more, and particularly preferably 30° or more.

[0022] The contact angle of the porous membrane with water in this specification is a value measured from the side after 1 minute by dropping 50 μL of ion-exchanged water onto the surface of the porous membrane. The contact angle can be measured by a general measuring device such as a dynamic contact angle meter "1100DAT" (product name) manufactured by Fibro.

[0023] The air permeability of the porous membrane used as a separator of the aqueous electrolyte battery is 3000sec / 100mL or less, preferably 1000sec / 100mL or less, and particularly preferably 600sec / 100mL or less. When the air permeability of the porous membrane satisfies such a value and the contact angle with water satisfies the above value, the porous membrane can be used as a separator to improve the load characteristics of the battery as described above. However, when a porous membrane with too small air permeability is used as a separator, the battery is likely to have a micro-short circuit. Therefore, from the viewpoint of suppressing the occurrence of a micro-short circuit and improving the reliability of the battery, the air permeability of the porous membrane used as a separator is 10sec / 100mL or more, preferably 20sec / 100mL or more, and particularly preferably 50sec / 100mL or more. When the separator is composed of a plurality of layers, each layer may be configured so that the air permeability of the separator as a whole is within the above range.

[0024] The air permeability of the porous membrane referred to in this specification is a value determined by the Gurley method specified in JIS P 8117.

[0025] In addition, the porous membrane used as a separator in an aqueous electrolyte battery has a thickness of 5 μm or more from the viewpoint of effectively suppressing the occurrence of micro-short circuits in the battery, and has a thickness of 100 μm or less, and preferably 30 μm or less, from the viewpoint of suppressing a decrease in the volumetric capacity density of the battery due to an increase in the thickness of the separator.

[0026] The porous membrane used as the separator is made of resin. Either resin with high affinity to water or resin with low affinity to water can be used for the porous membrane, but it is preferable to use polyolefins (polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, etc.) that are commonly used for battery separators.

[0027] As the porous membrane, a microporous membrane made of the above-mentioned resin (a porous membrane called a "microporous membrane" that is generally used as a separator for a battery) can be used.

[0028] The porous membrane may be selected from porous membranes such as microporous membranes made of the above-mentioned resins, which satisfy the above-mentioned air permeability and thickness. In the case of a microporous membrane made of a resin, the air permeability can be adjusted by adjusting the porosity or tortuosity of the pores.

[0029] In addition, polyolefins and the like, which are suitable as the resins constituting the porous membrane, have low affinity to water, and the contact angle of the porous membrane formed from them exceeds the upper limit value. However, in the case of the porous membrane made of such a resin, if the contact angle of the porous membrane with water is made to satisfy the above value by carrying out hydrophilization treatment, it can be used as a separator.

[0030] Examples of the hydrophilization treatment of the porous membrane include a method of introducing sulfonic acid groups into the constituent resin of the porous membrane by sulfuric acid treatment, and a method of treatment with a reactive gas containing fluorine gas and oxygen atoms and / or sulfur atoms (both of these methods are disclosed in JP-A-2000-355633, etc.). In addition, the hydrophilization treatment of the porous membrane can also be performed by a general method of hydrophilizing a resin film, such as a corona discharge treatment or an atmospheric pressure plasma treatment.

[0031] The aqueous electrolyte battery of the present invention is not particularly limited in other configurations as long as the electrolyte is an aqueous electrolyte and the porous membrane is used as a separator. That is, the aqueous electrolyte battery of the present invention can take the form of various batteries having an aqueous electrolyte, such as an alkaline battery (an alkaline primary battery, an alkaline secondary battery); a manganese battery; an air battery; etc. The alkaline battery includes a nickel-zinc battery using nickel oxyhydroxide as a positive electrode active material and a zinc-based material (a zinc material and a zinc alloy material are collectively referred to as such) as a negative electrode active material; a silver-zinc battery using silver oxide as a positive electrode active material and a zinc-based material as a negative electrode active material; etc.

[0032] The electrolyte of the aqueous electrolyte battery is an aqueous solution in which an electrolyte salt is dissolved in water as a solvent. The aqueous solution used as the electrolyte is not particularly limited, and it is possible to use a high-concentration alkaline electrolyte (pH: about 14) used in an alkaline dry battery. However, from the viewpoint of reducing the environmental load at the time of disposal and ensuring safety in the event of leakage of the electrolyte due to damage to the exterior body, it is preferable that the pH of the electrolyte is as close to neutral as possible, and the pH is preferably 3 or more, more preferably 5 or more, and also preferably less than 12, more preferably 10 or less, and even more preferably less than 7 from the viewpoint of inhibiting corrosion of the negative electrode active material.

[0033] Examples of the electrolyte salt of the aqueous solution used as the electrolyte include chlorides such as sodium chloride, potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, and zinc chloride; hydroxides of alkali metals and alkaline earth metals (lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, etc.), acetates (sodium acetate, potassium acetate, magnesium acetate, etc.), nitrates (sodium nitrate, potassium nitrate, magnesium nitrate, etc.), sulfates (sodium sulfate, potassium sulfate, magnesium sulfate, etc.), phosphates (sodium phosphate, potassium phosphate, magnesium phosphate, etc.), ), borates (sodium borate, potassium borate, magnesium borate, etc.), citrates (sodium citrate, potassium citrate, magnesium citrate, etc.), glutamate (sodium glutamate, potassium glutamate, magnesium glutamate, etc.); alkali metal bicarbonates (sodium bicarbonate, potassium bicarbonate, etc.); alkali metal percarbonates (sodium percarbonate, potassium percarbonate, etc.); compounds containing halogens such as fluorides; polyvalent carboxylic acids; and the aqueous solution may contain one or more of these electrolyte salts.

[0034] As the electrolyte salt, a salt of a strong acid selected from hydrochloric acid, sulfuric acid, and nitric acid and a weak base represented by ammonia or a hydroxide of a metal element such as aluminum hydroxide or magnesium hydroxide is preferable, and it is more preferable to use an ammonium salt or a salt of a specific metal element. - , SO4 2- , HSO4 - and NO3 - and at least one ion selected from Al ion, Mg ion, Fe ion, and ammonium ion. Examples of such ions include ammonium salts such as ammonium sulfate, ammonium hydrogen sulfate [(NH4)HSO4], ammonium chloride, and ammonium nitrate; aluminum salts such as aluminum sulfate, aluminum chloride, and aluminum nitrate; magnesium salts such as magnesium sulfate, magnesium chloride, magnesium chloride hydroxide [MgCl(OH)], and magnesium nitrate; and iron salts such as iron (II) sulfate, ammonium iron (II) sulfate [(NH4)2Fe(SO4)2], iron (III) sulfate, iron (II) chloride, and iron (II) nitrate.

[0035] In the negative electrode of an aqueous electrolyte battery, a metallic material such as a metal or an alloy is usually used as the negative electrode active material. However, an electrolyte consisting of an aqueous solution containing a salt of a strong acid and a weak base as exemplified above has a relatively weak corroding effect on the metallic material that is the negative electrode active material, compared to an electrolyte containing a salt of a strong acid and a strong base such as sodium chloride. In addition, an electrolyte containing a salt of a metal element selected from Al, Mg, and Fe, or an ammonium salt, among salts of strong acids, has a relatively high electrical conductivity compared to, for example, an aqueous zinc chloride solution. Therefore, as a salt of a strong acid and a weak base, Cl - , SO4 2- , HSO4 - and NO3 - When an electrolyte solution consisting of an aqueous solution containing a salt of at least one ion selected from the group consisting of Al ions, Mg ions, Fe ions, and ammonium ions is used, the discharge characteristics of the aqueous electrolyte battery can be further improved.

[0036] However, Cl - Ions and Fe 3+ Regarding salts with ions [iron(III) chloride], since it has a stronger corroding effect on the metal material that is the negative electrode active material than salts with other ion combinations, it is preferable to use a salt other than iron(III) chloride, and since it has a weaker corroding effect on the metal material that is the negative electrode active material, it is more preferable to use an ammonium salt.

[0037] Moreover, among the salts of the strong acid and the weak base, perchlorates pose a risk of combustion or explosion when heated or impacted. From the viewpoint of environmental load and safety during disposal, therefore, it is preferable that the aqueous solution does not contain perchlorate ions, or that the amount of perchlorate ions contained therein is small (preferably less than 100 ppm, and more preferably less than 10 ppm).

[0038] Furthermore, among the salts of strong acids and weak bases, many heavy metal salts (excluding iron salts), such as zinc chloride and copper sulfate, are harmful. From the viewpoint of environmental load and safety during disposal, it is preferable that they are not contained in the aqueous solution, or that even if they are contained, the amount of heavy metal ions other than iron ions is small (preferably less than 100 ppm, and more preferably less than 10 ppm).

[0039] In addition, when the aqueous electrolyte battery is an air battery, the aqueous solution usable as the electrolyte preferably contains a water-soluble high-boiling point solvent having a boiling point of 150°C or more as a solvent together with water. In an air battery, when the remaining capacity of the negative electrode decreases due to discharge, the voltage decreases accordingly, but in the later stage of discharge when the remaining capacity decreases, the voltage tends to decrease and fluctuate greatly. However, when the aqueous solution contains a water-soluble high-boiling point solvent, the voltage fluctuation in the later stage of discharge can be suppressed, resulting in an air battery with better discharge characteristics. The upper limit of the boiling point of the water-soluble high-boiling point solvent is usually 320°C.

[0040] The water-soluble high-boiling point solvent preferably has a high surface tension and dielectric constant. Specific examples include polyhydric alcohols such as ethylene glycol (boiling point 197°C, surface tension 48mN / m, dielectric constant 39), propylene glycol (boiling point 188°C, surface tension 36mN / m, dielectric constant 32), and glycerin (boiling point 290°C, surface tension 63mN / m, dielectric constant 43); polyalkylene glycols such as PEG (for example, boiling point 230°C, surface tension 43mN / m, dielectric constant 35) (preferably with a molecular weight of 600 or less); and the like. The electrolyte solution may use only one of these water-soluble high-boiling point solvents, or may use two or more of them in combination, but it is more preferable to use glycerin.

[0041] When using a water-soluble high-boiling point solvent, from the viewpoint of ensuring the effect of its use, the content of the water-soluble high-boiling point solvent in the total solvent of the aqueous solution is preferably 1% by mass or more, more preferably 3% by mass or more. However, if the amount of the water-soluble high-boiling point solvent in the aqueous solution is too large, the ionic conductivity of the aqueous solution may become too small, which may deteriorate the battery characteristics, so the content of the water-soluble high-boiling point solvent in the total solvent of the aqueous solution is preferably 30% by mass or less, more preferably 20% by mass or less.

[0042] The concentration of the electrolyte salt in the aqueous solution may be any concentration that allows the electrical conductivity of the aqueous solution to be adjusted to about 80 to 700 mS / cm, and is usually 5 to 50 mass %.

[0043] The aqueous solution used as the electrolyte preferably contains an indium compound dissolved in its solvent (water or a mixed solvent of water and a water-soluble high-boiling point solvent).When an indium compound is dissolved in the aqueous solution, the generation of hydrogen gas in the battery can be effectively suppressed.

[0044] Examples of the indium compound to be dissolved in the aqueous solution include indium hydroxide, indium oxide, indium sulfate, indium sulfide, indium nitrate, indium bromide, and indium chloride.

[0045] The concentration of the indium compound in the aqueous solution is, by mass, preferably 0.005% or more, more preferably 0.01% or more, and particularly preferably 0.05% or more, and is preferably 1% or less, more preferably 0.5% or less, and particularly preferably 0.1% or less.

[0046] In addition to the above-mentioned components, various known additives may be added to the aqueous solution as necessary within the range that does not impair the effects of the present invention. For example, zinc oxide may be added to prevent corrosion (oxidation) of the metal material used in the negative electrode.

[0047] The aqueous solution constituting the electrolyte may be gelled, and it is also preferable to use a gelled electrolyte (gelled electrolyte) obtained by blending the aqueous solution containing an electrolyte salt and having a pH of 3 or more and less than 12 with a thickener (sodium polyacrylate, carboxymethyl cellulose, etc.) as the electrolyte for the aqueous electrolyte battery. In this case as well, the discharge characteristics of the aqueous electrolyte battery can be improved by suppressing the fluctuation in voltage during the latter stage of discharge, and since the volatilization of water from the gelled electrolyte is suppressed, it is possible to suppress the deterioration of discharge characteristics due to the compositional fluctuation of the electrolyte, particularly in air batteries in which air holes are formed in the exterior body, and it is also possible to further improve the storage characteristics of the battery.

[0048] When the aqueous electrolyte battery is an alkaline battery or a manganese battery, the positive electrode may have a structure in which a positive electrode mixture layer containing a positive electrode active material, a conductive additive, and a binder is provided on one or both sides of a current collector.

[0049] Examples of the positive electrode active material that can be used when the aqueous electrolyte is an alkaline battery include silver oxide (silver(I) oxide, silver(II) oxide, etc.), manganese oxides such as manganese dioxide, nickel oxyhydroxide, composite oxides of silver and cobalt, nickel or bismuth, etc. In addition, when the sheet-shaped battery is a manganese battery, manganese oxides such as manganese dioxide are used as the positive electrode active material.

[0050] Examples of the conductive assistant for the positive electrode mixture layer that can be used include carbon materials such as acetylene black; ketjen black; carbon blacks such as channel black, furnace black, lamp black, and thermal black; and carbon fibers; as well as conductive fibers such as metal fibers; carbon fluoride; metal powders such as copper and nickel; and organic conductive materials such as polyphenylene derivatives.

[0051] Examples of the binder for the positive electrode mixture layer include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polyvinylpyrrolidone (PVP).

[0052] The positive electrode mixture layer preferably contains 80 to 98% by mass of positive electrode active material, 1.5 to 10% by mass of conductive additive, and 0.5 to 10% by mass of binder. The thickness of the positive electrode mixture layer (thickness per surface of the current collector) is preferably 30 to 300 μm.

[0053] A positive electrode having a positive electrode mixture layer can be manufactured, for example, by dispersing a positive electrode active material, a conductive assistant, a binder, and the like in water or an organic solvent such as N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture-containing composition (slurry, paste, etc.) (the binder may be dissolved in the solvent), applying this onto a current collector, drying it, and, if necessary, subjecting it to a pressing process such as a calendaring process.

[0054] When the aqueous electrolyte battery is an air battery, the positive electrode may have a catalyst layer, for example, a structure in which a catalyst layer and a current collector are laminated.

[0055] The catalyst layer may contain a catalyst, a binder, and the like.

[0056] Examples of the catalyst for the catalyst layer include silver, platinum group metals or alloys thereof, transition metals, platinum / metal oxides such as Pt / IrO2, La1-x Ca x Examples include perovskite oxides such as CoO3, carbides such as WC, nitrides such as Mn4N, manganese oxides such as manganese dioxide, and carbon (graphite, carbon black (acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, etc.), charcoal, activated carbon, etc.), and one or more of these are used.

[0057] The catalyst layer preferably contains 1% by mass or less of heavy metals, excluding the components of the electrolyte. In the case of a positive electrode having a catalyst layer with such a low content of heavy metals, the battery can be disposed of without any special treatment, resulting in a battery with low environmental impact.

[0058] The content of heavy metals in the catalyst layer as referred to in this specification can be measured by fluorescent X-ray analysis. For example, it can be measured using Rigaku's "ZSX100e" under the conditions of excitation source: Rh50kV, and analysis area: φ10mm.

[0059] Therefore, it is recommended that the catalyst for the catalyst layer not contain heavy metals, and it is more preferable to use the various carbons mentioned above.

[0060] In order to further increase the reactivity of the positive electrode, the specific surface area of ​​the carbon used as the catalyst is set to 200 m 2 / g or more, and 2 / g or more is more preferable, and 500m 2 / g or more is more preferable. The specific surface area of ​​carbon referred to in this specification is a value determined by the BET method in accordance with JIS K 6217, and can be measured, for example, using a specific surface area measuring device ("Macsorb HM model e-1201" manufactured by Mountech Co., Ltd.) using the nitrogen adsorption method. The upper limit of the specific surface area of ​​carbon is usually 2000 m 2 / g.

[0061] The catalyst content in the catalyst layer is preferably 20 to 70 mass %.

[0062] Examples of the binder for the catalyst layer include fluororesin binders such as PVDF, PTFE, vinylidene fluoride copolymers and tetrafluoroethylene copolymers [vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), vinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), vinylidene fluoride-tetrafluoroethylene copolymer (PVDF-TFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (PVDF-HFP-TFE), etc.]. Among these, tetrafluoroethylene polymer (PTFE) or copolymer is preferred, and PTFE is more preferred. The content of the binder in the catalyst layer is preferably 3 to 50 mass%.

[0063] In the case of a positive electrode having a catalyst layer, for example, the catalyst, binder, etc. can be mixed with water, rolled with a roll, and attached to a current collector. Alternatively, the catalyst and the binder used as needed can be dispersed in water or an organic solvent to prepare a catalyst layer forming composition (slurry, paste, etc.), which is applied to the surface of a current collector, dried, and then, if necessary, subjected to a pressing process such as a calendaring process.

[0064] For the current collector for the positive electrode having a positive electrode mixture layer or the positive electrode having a catalyst layer, for example, a metal mesh, foil, expanded metal, punched metal, etc. of titanium, nickel, stainless steel, copper, etc., a carbon mesh, sheet, etc. can be used. The thickness of the current collector for the positive electrode is preferably 10 μm or more and 300 μm or less.

[0065] In addition, when a sheet-shaped exterior body made of a resin film (described in detail later) is used as the exterior body of the battery, the resin film constituting the sheet-shaped exterior body can also be used as the current collector of the positive electrode. In this case, for example, a carbon paste is applied to the surface of the resin film that is expected to become the inner surface of the sheet-shaped exterior body to form a current collector, and a positive electrode mixture layer and a catalyst layer are formed on this surface in the same manner as above to form a positive electrode. The thickness of the carbon paste layer is preferably 30 to 300 μm.

[0066] The negative electrode of an aqueous electrolyte battery contains a metal material such as a zinc-based material (zinc or zinc alloy), a magnesium-based material (magnesium or magnesium alloy), an aluminum-based material (aluminum or aluminum alloy), etc. In such a negative electrode, the metal such as zinc, magnesium, or aluminum acts as the active material.

[0067] In addition, in consideration of reducing the environmental load when disposing of batteries, it is preferable that the metal material used for the negative electrode contains small amounts of mercury, cadmium, lead, and chromium, and it is more preferable that the specific contents, on a mass basis, are mercury: 0.1% or less, cadmium: 0.01% or less, lead: 0.1% or less, and chromium: 0.1% or less.

[0068] As a specific example of the negative electrode containing a metal material, a metal sheet such as a sheet made of the above material (zinc foil, zinc alloy foil, magnesium foil, magnesium alloy foil, aluminum foil, aluminum alloy foil, etc.) is preferably used. In the case of such a negative electrode, the thickness thereof is preferably 10 to 500 μm.

[0069] Examples of alloy components of the zinc alloy include indium, bismuth, and aluminum, and an alloy containing one or more of the above elements is used.

[0070] The indium content in the zinc alloy is, for example, 0.005% or more and 0.1% or less by mass, the bismuth content is, for example, 0.002% or more and 0.2% or less by mass, and the aluminum content is, for example, 0.001% or more and 0.15% or less by mass.

[0071] In addition, as zinc foil (zinc alloy foil), there are electrolytic zinc foil and rolled zinc foil, and electrolytic zinc foil is preferably used because electrolytic zinc foil is less likely to generate gas due to reaction with the electrolyte in the battery, and electrolytic zinc foil containing bismuth is more preferably used. The preferred range of the bismuth content in the electrolytic zinc foil is 0.02% or more and 0.1% or less by mass.

[0072] Furthermore, examples of alloy components of magnesium alloys include calcium, manganese, zinc, and aluminum, and an alloy containing one or more of the above elements is used.

[0073] The calcium content in the magnesium alloy is, for example, 1% or more and 3% or less by mass, the manganese content is, for example, 0.1% or more and 0.5% or less by mass, the zinc content is, for example, 0.4% or more and 1% or less by mass, and the aluminum content is, for example, 8% or more and 10% or less by mass.

[0074] Furthermore, examples of alloy components of the aluminum alloy include zinc, tin, gallium, silicon, iron, magnesium, and manganese, and an alloy containing one or more of the above elements is used.

[0075] The zinc content in the aluminum alloy is, for example, 0.5% or more and 10% or less by mass. The tin content is, for example, 0.04% or more and 1.0% or less by mass. The gallium content is, for example, 0.003% or more and 1.0% or less by mass. The silicon content is, for example, 0.05% or less by mass. The iron content is, for example, 0.1% or less by mass. The magnesium content is, for example, 0.1% or more and 2.0% or less by mass. The manganese content is, for example, 0.01% or more and 0.5% or less by mass.

[0076] Specific examples of negative electrodes containing a metal material include negative electrodes containing metal particles such as particles made of the above-mentioned materials.

[0077] In the case of a negative electrode containing metal particles, the metal particles may be of one type alone or of two or more types.

[0078] Regarding the particle size of the zinc-based material, for example, the proportion of particles having a particle size of 75 μm or less among all particles is preferably 50 mass% or less, more preferably 30 mass% or less, and the proportion of particles having a particle size of 100 to 200 μm is 50 mass% or more, more preferably 90 mass% or more.

[0079] Regarding the particle size of the magnesium-based material particles and the aluminum-based material particles, for example, the proportion of particles having a particle size of 30 μm or less among all particles is preferably 50 mass% or less, more preferably 30 mass% or less, and the proportion of particles having a particle size of 50 to 200 μm is 50 mass% or more, more preferably 90 mass% or more.

[0080] The particle size of metal particles in this specification is the particle size at a cumulative frequency of 50% on a volume basis, measured by dispersing the particles in a medium that does not dissolve the particles using a laser scattering particle size distribution analyzer (e.g., HORIBA LA-920). 50 ).

[0081] In the case of the negative electrode containing the metal particles, a gelling agent (polyethylene oxide, sodium polyacrylate, carboxymethyl cellulose, etc.) and a binder may be added as necessary, and a negative electrode agent (gelled negative electrode, etc.) formed by adding an electrolyte solution to the gelling agent may be used. The amount of the gelling agent in the negative electrode is preferably 0.5 to 1.5 mass%, and the amount of the binder is preferably 0.5 to 3 mass%.

[0082] The electrolyte for the negative electrode containing metal particles may be the same as that injected into the battery.

[0083] The content of metal particles in the negative electrode is, for example, preferably 60% by mass or more, more preferably 65% ​​by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less.

[0084] The negative electrode containing metal particles preferably contains an indium compound, which makes it possible to more effectively prevent hydrogen gas generation due to a corrosion reaction between the metal particles and the electrolyte.

[0085] Examples of the indium compound include indium oxide and indium hydroxide.

[0086] The amount of the indium compound used in the negative electrode is preferably 0.003 to 1 per 100 metal particles in terms of mass ratio.

[0087] In addition, a current collector may be used for the negative electrode containing a metal material, if necessary. Examples of the current collector for the negative electrode containing a metal material include a mesh, foil, expanded metal, punched metal, etc., of a metal such as nickel, copper, or stainless steel; a carbon sheet or mesh; etc. The thickness of the current collector for the negative electrode is preferably 10 μm or more and 300 μm or less.

[0088] When a sheet-like exterior body made of a resin film is used as the exterior body of the battery, the negative electrode current collector can be used by applying a carbon paste to the surface that is to become the inner surface of the sheet-like exterior body, as in the case of the positive electrode. The thickness of the carbon paste layer is preferably 50 to 200 μm.

[0089] There are no particular limitations on the form of the aqueous electrolyte battery, and the battery may be in any form, such as a flat type (including a coin type and a button type) having a battery case in which the outer can and the sealing plate are crimped and sealed via a gasket, or the outer can and the sealing plate are sealed by welding together; a sheet type having a sheet-like outer body made of a resin film; or a cylindrical type (cylindrical type, square type (square cylindrical type)) having a battery case in which the outer can and the sealing plate are crimped and sealed via a gasket, or the outer can and the sealing plate are sealed by welding together.

[0090] When the aqueous electrolyte battery is used as a power source for medical and health equipment, such as a patch that can be worn on the body, particularly a patch that is worn on the surface of the skin to measure body conditions such as body temperature, pulse rate, and sweat rate, it is preferable to make the battery a sheet-like battery having a sheet-like exterior body made of a resin film.

[0091] The sheet-like exterior body is made of a resin film, and examples of such a resin film include nylon film (such as nylon 66 film) and polyester film (such as polyethylene terephthalate (PET) film).

[0092] In addition, the sheet-like outer packaging is generally sealed by heat-sealing the end of the upper resin film and the end of the lower resin film of the sheet-like outer packaging, but in order to make this heat-sealing easier, a heat-sealing resin layer may be laminated on the resin film exemplified above and used for the sheet-like outer packaging, or the separator may be sandwiched between the upper and lower heat-sealing resin layers and heat-sealed. Examples of heat-sealing resins constituting the heat-sealing resin layer include modified polyolefin films (such as modified polyolefin ionomer films), polypropylene and copolymers thereof. The thickness of the heat-sealing resin layer is preferably 20 to 200 μm.

[0093] A metal layer may be laminated on the resin film. The metal layer may be made of an aluminum film (aluminum foil, including aluminum alloy foil), a stainless steel film (stainless steel foil), etc. The thickness of the metal layer is preferably 10 to 150 μm.

[0094] Furthermore, the resin film constituting the sheet-like exterior body may be a film having a configuration in which the above-mentioned heat-sealable resin layer and the above-mentioned metal layer are laminated together.

[0095] It is also preferable that the resin film constituting the sheet-like exterior body has an electrically insulating water vapor barrier layer. In this case, the electrically insulating resin film may have a single-layer structure in which the film itself also serves as a water vapor barrier layer, or a multilayer structure having a plurality of electrically insulating resin film layers, at least one of which serves as a water vapor barrier layer, or a multilayer structure having an electrically insulating water vapor barrier layer on the surface of a base layer made of a resin film.

[0096] Among such resin films, those in which a water vapor barrier layer made of at least an inorganic oxide is formed on the surface of a base layer made of a resin film are preferably used.

[0097] Examples of inorganic oxides constituting the water vapor barrier layer include aluminum oxide and silicon oxide. Note that a water vapor barrier layer made of silicon oxide tends to have a higher function of suppressing the permeation of moisture in the electrolyte in the battery than a water vapor barrier layer made of aluminum oxide. Therefore, it is more preferable to adopt silicon oxide as the inorganic oxide constituting the water vapor barrier layer.

[0098] The water vapor barrier layer made of an inorganic oxide can be formed on the surface of the base layer by, for example, a vapor deposition method. The thickness of the water vapor barrier layer is preferably 10 to 300 nm.

[0099] The base layer of the resin film having a water vapor barrier layer may be the above-mentioned nylon film or polyester film, or may be a polyolefin film, a polyimide film, a polycarbonate film, etc. The thickness of the base layer is preferably 5 to 100 μm.

[0100] In the case of a resin film having a water vapor barrier layer and a base layer, a protective layer for protecting the water vapor barrier layer may be formed on the surface of the water vapor barrier layer (the surface opposite to the base layer).

[0101] In the case of a resin film having a water vapor barrier layer and a substrate layer, the above-mentioned heat-sealable resin layer may be further laminated thereon.

[0102] The overall thickness of the resin film is preferably 10 μm or more from the viewpoint of providing sufficient strength to the battery, and is preferably 200 μm or less from the viewpoint of preventing an increase in the battery thickness and a decrease in energy density.

[0103] The water vapor permeability of the resin film that constitutes the sheet-like exterior body is 10 g / m 2 It is preferable that the resin film does not transmit water vapor as much as possible, that is, the water vapor transmission rate is preferably as low as possible, and is preferably 0 g / m 2· May be 24 hours.

[0104] The water vapor permeability of the resin film referred to in this specification is a value measured in accordance with JIS K 7129B method.

[0105] In addition, when the aqueous electrolyte battery is an air battery, it is preferable that the resin film constituting the sheet-shaped exterior body has a certain degree of oxygen permeability. In an air battery, air (oxygen) is supplied to the positive electrode to discharge the battery, so air holes for introducing oxygen into the battery are formed in the sheet-shaped exterior body. When the resin film constituting the sheet-shaped exterior body has oxygen permeability, oxygen can be introduced into the battery through the exterior body from places other than the air holes of the sheet-shaped exterior body, so that oxygen is supplied more uniformly throughout the positive electrode, improving the discharge characteristics of the battery and lengthening the discharge time. In addition, it is also possible to realize a sheet-shaped air battery that does not have air holes in the sheet-shaped exterior body.

[0106] When the aqueous electrolyte battery is an air battery, the specific oxygen permeability of the resin film constituting the sheet-like outer casing is 0.02 cm 3 / m 2 ·24h·MPa or more is preferable, and 0.2cm 3 / m 2 However, if the battery is an air battery, if the resin film constituting the sheet-like outer casing is permeable to too much oxygen, self-discharge may occur and the capacity may be lost. Therefore, the oxygen permeability of the resin film is set to 100 cm 3 / m 2 ·24h·MPa or less is preferable, and 50cm 3 / m 2 It is more preferable that the resistance is 24h·MPa or less.

[0107] On the other hand, when the aqueous electrolyte battery is a battery other than an air battery, there is no particular restriction on the oxygen permeability of the resin film constituting the sheet-like exterior body. However, from the viewpoint of improving the storage stability of the battery, it is preferable that the resin film does not allow much oxygen to pass through. The oxygen permeability of the specific resin film is 10 cm 3 / m 2 It is preferable that the compressive strength is 24h·MPa or less.

[0108] The oxygen permeability of the resin film referred to in this specification is a value measured in accordance with JIS K 7126-2.

[0109] Furthermore, when using an exterior body that is crimp-sealed, the material of the gasket interposed between the exterior can and the sealing plate can be polypropylene, nylon, or other materials that are used in alkaline batteries, etc.

[0110] In addition, in order to prevent elements such as iron constituting the outer can from eluting during charging, it is desirable to plate the inner surface of the outer can with a corrosion-resistant metal such as tin, zinc, or indium.

[0111] An example of the aqueous electrolyte battery of the present invention is shown typically in Figures 1 and 2. Figures 1 and 2 show an example in which the aqueous electrolyte battery is an air battery having a sheet-like exterior body (sheet-like air battery), with Figure 1 showing a plan view thereof and Figure 2 showing a cross-sectional view taken along line II in Figure 1.

[0112] As shown in Fig. 2, in the aqueous electrolyte battery 1, a positive electrode 10, a separator 30, a negative electrode 20, and an electrolyte (not shown) are contained in a sheet-like exterior body 50. Note that the dotted line in Fig. 1 indicates the size of the positive electrode 10 contained in the sheet-like exterior body 50 (the size of the wide main body part excluding the terminal part, which corresponds to the size of the catalyst layer of the positive electrode).

[0113] A terminal portion 10a of the positive electrode 10 and a terminal portion 20a of the negative electrode 20 protrude from the upper side of the sheet-like exterior body 50 in the figure. These terminal portions 10a, 20a are used as external terminals for electrically connecting the aqueous electrolyte battery 1 to an applicable device.

[0114] The sheet-like exterior body 50 has multiple air holes 51 for introducing air into the positive electrode on one side thereof on which the positive electrode 10 is arranged, and a water-repellent film 40 is arranged on the sheet-like exterior body 50 side of the positive electrode 10 to prevent leakage of the electrolyte through the air holes 51.

[0115] The positive electrode 10 has a catalyst layer, and as described above, for example, has a structure in which the catalyst layer is laminated with a current collector, but in order to avoid complicating the drawing, the layers of the positive electrode 10 are not shown separately in Fig. 2. Also, in Fig. 2, the sheet-like exterior body 50 (the resin film constituting it) is shown as a single-layer structure, but as described above, the resin film constituting the sheet-like exterior body can also have a multi-layer structure.

[0116] The terminal portion of the positive electrode may be provided by a positive electrode current collector having a shape including a main portion where the positive electrode mixture layer and / or catalyst layer are formed, and an exposed portion where the positive electrode mixture layer and / or catalyst layer are not formed, or may be provided by attaching a separate lead body to the positive electrode current collector by welding or the like.

[0117] Furthermore, in the case of a negative electrode having a negative electrode current collector, the terminal portion of the negative electrode can be formed by forming the negative electrode current collector into a shape having a main portion in which a layer containing a negative electrode active material or the like is formed, and an exposed portion in which this layer is not formed, and providing the terminal portion using this exposed portion, or by attaching a separate lead body to the negative electrode current collector by welding or the like.

[0118] In addition, when the negative electrode is composed of a metal sheet, the metal sheet can be cut into a shape having a main body portion and a terminal portion that function as the negative electrode active material layer, thereby forming a negative electrode having a main body portion and a terminal portion from a single metal sheet.

[0119] The shape of the sheet-like exterior body may be polygonal (triangle, quadrangle, pentagon, hexagon, heptagon, octagon) in plan view, or may be circular or elliptical in plan view. In the case of a sheet-like exterior body that is polygonal in plan view, the positive electrode terminal and the negative electrode terminal may be drawn to the outside from the same side, or each may be drawn to the outside from a different side.

[0120] When the aqueous electrolyte battery is an air battery, a water-repellent film is usually disposed between the positive electrode and the exterior body as shown in Fig. 2. The water-repellent film is made of a film that is water-repellent but allows air to pass through. Specific examples of such water-repellent films include films made of resins such as fluororesins such as PTFE; polyolefins such as polypropylene and polyethylene; etc. The thickness of the water-repellent film is preferably 50 to 250 µm.

[0121] In addition, when the aqueous electrolyte battery is an air battery, an air diffusion membrane for supplying air taken into the exterior body to the positive electrode may be disposed between the exterior body and the water-repellent film. The air diffusion membrane may be a nonwoven fabric made of a resin such as cellulose, polyvinyl alcohol, polypropylene, or nylon. The thickness of the air diffusion membrane is preferably 100 to 250 μm.

[0122] When the aqueous electrolyte battery is a sheet-type battery, there is no particular restriction on its thickness (the length of a in FIG. 2) and it can be changed appropriately depending on the application of the battery. One advantage of a sheet-type battery is that it can be made thin, and from this viewpoint, it is preferable that the thickness is, for example, 1 mm or less. When the aqueous electrolyte battery is a sheet-type air battery, it is particularly easy to provide such a thin battery.

[0123] There is also no particular lower limit on the thickness of the sheet-type battery, but in order to ensure a certain capacity, it is usually preferable that the thickness is 0.2 mm or more. EXAMPLES

[0124] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0125] Example 1 <Positive electrode> DBP oil absorption 495cm 3 / 100g, specific surface area 1270m 2 A composition for forming a catalyst layer was prepared by mixing 30 parts by mass of carbon (Ketjen Black EC600JD (Lion Specialty Chemicals)) of 1.0 g / g, 15 parts by mass of an acrylic dispersant, 60 parts by mass of SBR, and 500 parts by mass of water.

[0126] A porous carbon paper (thickness: 0.25 mm, porosity: 75%) was used as a current collector, and the catalyst layer forming composition was applied in an amount of 10 mg / cm 2 after drying. 2 The substrate surface was coated with the solution in stripes so that the solution was dried, thereby obtaining a current collector having a portion where the catalyst layer was formed and a portion where the catalyst layer was not formed. This current collector was punched out to have a catalyst layer size of 15 mm x 15 mm and a lead portion of 5 mm x 15 mm at one end where the catalyst layer was not formed, thereby producing a positive electrode (air electrode) with an overall thickness of 0.27 mm.

[0127] <Negative electrode> A zinc alloy foil (thickness: 0.05 mm) containing 0.05% In, 0.04% Bi, and 0.001% Al as additive elements was punched out into a shape having a 15 mm x 15 mm portion that would function as the active material and a 5 mm x 15 mm portion at one end that would serve as a lead portion to prepare a negative electrode.

[0128] <Electrolyte> Glycerin was added to an aqueous solution of ammonium sulfate with a concentration of 20% by mass in an amount that would make the total amount with water 10% by mass to prepare an electrolyte (pH 5.3 measured at 25°C using a "LAQUA twin compact pH meter" manufactured by Horiba, Ltd. The electrolytes of the sheet-type air batteries of all the examples and comparative examples described below also had the same pH value determined by the same measurement method). The concentrations of perchlorate ions and heavy metal ions excluding iron ions in the electrolyte were each less than 100 ppm. The same is true for the electrolytes of the sheet-type air batteries of Examples 2 and 3 and Comparative Examples 1 to 3 described below.

[0129] <separator> The separator used was a hydrophilized microporous PE membrane (thickness: 16 μm, air permeability: 45 sec / 100 mL, contact angle with water: 65°). The hydrophilization of the microporous PE membrane was performed by introducing sulfonic acid groups into the PE constituting the microporous membrane through sulfuric acid treatment, and further treating the membrane with a mixed gas containing fluorine gas, oxygen, sulfur dioxide, and nitrogen.

[0130] <Water-repellent film> The water-repellent film used was a PTFE sheet with a thickness of 200 μm.

[0131] <Battery assembly> Two sheets of aluminum laminate film (thickness: 65 μm) measuring 25 mm×25 mm and having a PET film on the outer surface of the aluminum foil and a PP film as a heat-sealable resin layer on the inner surface were used as the exterior body.

[0132] Nine air holes with a diameter of 0.2 mm were formed in a regular pattern of three at equal intervals of 4.8 mm length × 4.8 mm width (the center-to-center distance between air holes was 5 mm) in one exterior body arranged on the positive electrode side, and the water-repellent film was heat-welded to the inner surface using hot melt resin. In addition, a modified polyolefin ionomer film was attached parallel to the sides of the exterior body to the part where the positive and negative electrode leads were placed in order to improve the sealing of the heat-welded part between the leads and the exterior body in the other exterior body arranged on the negative electrode side.

[0133] The positive electrode, the separator, and the negative electrode were laminated in this order on the water-repellent film of the sheet-like exterior body with the water-repellent film facing down, and another exterior body was placed on top of it so that the modified polyolefin ionomer film was positioned on the leads of the positive electrode and the negative electrode. Next, the three peripheral sides of the two exterior bodies were heat-sealed together to form a bag, the electrolyte was poured in through the opening, and the opening was then heat-sealed to seal the bag, forming a sheet-like air battery (aqueous electrolyte battery).

[0134] Example 2 A sheet-type air battery was produced in the same manner as in Example 1, except that the separator was changed to a microporous PE membrane having a thickness of 20 μm, an air permeability of 150 sec / 100 mL, and a contact angle with water of 63°, which had been hydrophilized in the same manner as in Example 1.

[0135] Example 3 A sheet-type air battery was produced in the same manner as in Example 1, except that the separator was changed to a PE / PP / PE microporous membrane (a three-layer microporous membrane having a PE layer on both sides of a PP layer) that had been hydrophilized in the same manner as in Example 1, with a thickness of 25 μm, an air permeability of 550 sec / 100 mL, and a contact angle with water of 63°.

[0136] Comparative Example 1 A sheet-shaped air battery was produced in the same manner as in Example 1, except that the separator was changed to a PP nonwoven fabric having a thickness of 100 μm and an air permeability of 2 sec / 100 mL, which had been hydrophilized in the same manner as in Example 1. The contact angle of this hydrophilized PP nonwoven fabric with water could not be measured because the dropped ion-exchanged water immediately soaked into the nonwoven fabric.

[0137] Comparative Example 2 A sheet-shaped air battery was produced in the same manner as in Example 1, except that the separator was changed to one in which two graft films (thickness per film: 15 μm) composed of a graft copolymer having a structure in which acrylic acid is graft-copolymerized to a PE main chain were placed on both sides of a cellophane film (thickness: 20 μm) (total thickness: 50 μm). The air permeability of the entire separator exceeded the upper limit of measurement (>3000 sec / 100 mL).

[0138] Comparative Example 3 A sheet-type air battery was produced in the same manner as in Example 1, except that the separator was changed to a non-hydrophilized PE microporous membrane (thickness: 16 μm, air permeability: 150 sec / 100 mL, contact angle with water: 102°).

[0139] The sheet-shaped air batteries of the Examples and Comparative Examples were evaluated as follows.

[0140] [Pulse discharge test (load characteristic evaluation)] For each of the sheet-shaped air batteries of the Examples and Comparative Examples, a pulse discharge test was carried out 50 times under conditions of a current value of 30 mA, a pulse width of 10 msec, and a pulse interval of 3 sec, and the closed circuit voltage (CCV) was measured.

[0141] [OCV measurement before and after load test (reliability evaluation)] A 5 kg weight was placed on each of the sheet-air batteries of the Examples and Comparative Examples whose open circuit voltages (OCV) had been measured, and a load test was carried out for 30 days at 20° C. Then, the OCV of each battery after the load test was measured.

[0142] The configurations of the separators used in the sheet-type air batteries of the Examples and Comparative Examples are shown in Table 1, and the above-mentioned evaluation results are shown in Table 2. In Table 1, "-" in the "Contact angle with water" column means that the contact angle with water could not be measured.

[0143] [Table 1]

[0144] [Table 2]

[0145] As shown in Tables 1 and 2, the sheet-type air batteries of Examples 1 to 3, which used a resin porous membrane with suitable thickness, air permeability, and water contact angle as a separator, had high CCV during pulse discharge and good load characteristics.In addition, the change in OCV before and after the load test was small, the occurrence of micro-short circuits due to the application of load was suppressed, and they also had excellent reliability.

[0146] In contrast, the battery of Comparative Example 1, which used a separator made of a porous film (a hydrophilically treated PP nonwoven fabric) with too little air permeability, showed a large drop in OCV during the load test and was poor in reliability. Also, the battery of Comparative Example 2, which used a separator made of a laminate of a graft film and a cellophane film (both of which have no pores) with too much air permeability, and the battery of Comparative Example 3, which used a separator made of a porous film with too large a contact angle with water, showed low CCV during pulse discharge and poor load characteristics.

[0147] The present invention can be implemented in other forms than those described above without departing from the spirit of the present invention. The embodiments disclosed in this application are merely examples, and the present invention is not limited to these embodiments. The scope of the present invention shall be interpreted in accordance with the description of the appended claims rather than the description of the above specification, and all modifications within the scope of the claims are included in the scope of the claims. [Industrial Applicability]

[0148] The aqueous electrolyte battery of the present invention has a small environmental impact when the electrolyte is an aqueous solution, particularly when the aqueous solution has a suitable pH of 3 or more and less than 12, and is unlikely to cause any problems even if the electrolyte leaks due to breakage and comes into contact with the body. Therefore, the aqueous electrolyte battery of the present invention is suitable as a power source for medical and health devices, such as patches that can be worn on the body, particularly patches that are worn on the surface of the skin to measure body conditions such as body temperature, pulse rate, and sweat rate, and can also be used in the same applications as those in which batteries (primary batteries) having an aqueous electrolyte, such as conventionally known air batteries and alkaline batteries, are used. [Explanation of symbols]

[0149] 1 Aqueous electrolyte battery 10 Positive electrode (air electrode) 10a Positive electrode terminal 20 negative electrode 20a Negative electrode terminal 30 Separator 40 Water-repellent film 50 Sheet-shaped exterior body 51 Air vent

Claims

1. A battery comprising a positive electrode, a negative electrode containing a metal material, a separator, and an aqueous electrolyte solution housed in an exterior body, the separator is a porous film made of resin, having a thickness of 5 μm or more and 100 μm or less, an air permeability of 10 sec / 100 mL or more and 3000 sec / 100 mL or less, and a contact angle with water of 90° or less; The aqueous electrolyte battery according to claim 1, wherein the negative electrode comprises an electrolytic zinc foil.

2. 2. The aqueous electrolyte battery according to claim 1, wherein the separator has a contact angle with water of 70° or less.

3. 3. The aqueous electrolyte battery according to claim 1, wherein the separator has an air permeability of 10 sec / 100 mL or more and 1000 sec / 100 mL or less.

4. 4. The aqueous electrolyte battery according to claim 1, wherein the separator has a thickness of 5 μm or more and 30 μm or less.

5. 5. The aqueous electrolyte battery according to claim 1, wherein the porous membrane is made of polyolefin.

6. 6. The aqueous electrolyte battery according to claim 5, wherein the porous membrane is made of polyethylene or polypropylene.

7. 7. The aqueous electrolyte battery according to claim 1, which is an air battery.

8. 8. The aqueous electrolyte battery according to claim 1, which is a sheet-type battery having a resin film as an exterior body.

9. 9. The aqueous electrolyte battery according to claim 1, wherein the aqueous electrolyte has a pH of 3 or more and less than 12.

10. A patch that can be attached to the body, comprising the aqueous electrolyte battery according to any one of claims 1 to 9 as a power source.

Citation Information

Patent Citations

  • An air battery electrocatalyst, a preparation method and an application thereof

    CN109193000A

  • Secondary battery and manufacture of secondary battery

    JP1996088022A

  • Lithium ion battery

    JP2017027944A

  • Microporous membrane

    WO2013047600A1

  • Air cell and patch

    WO2018056307A1